High school and transition experiences of twice exceptional students with autism spectrum disorder: Parents’ perceptions - Madaus, Joseph; Tarconish, Emily; Langdon, Shannon W.; Gelbar, Nicholas (Frontiers in Psychology, 2022)
Students with autism spectrum disorder (ASD) are accessing college in increasing numbers. Within this cohort are students who are twice exceptional—those who are both academically talented and diagnosed with ASD. Little is known about factors and experiences that impact their successful transition to college. Parents play a critical role in the secondary transition process, but currently, there is a paucity of research that examines their perceptions of this experience. This study presents the results of semi-structured interviews with the parents of 10 college students with ASD who were enrolled in postsecondary institutions in the United States. The parents provided perceptions of their student’s best and most challenging aspects of high school, as well as of the transition preparation the student received. Suggestions were offered in regard to how transition services can be improved for this group of students. Implications for planning and practice are presented.